A bright cadmium-free, hybrid organic/quantum dot white light-emitting diode - Yang, Xuyong (2013)
We report a bright cadmium-free, InP-based quantum dot light-emitting diode (QD-LED) with efficient green emission. A maximum brightness close to 700 cd/m2 together with a relatively low turn-on voltage of 4.5 V has been achieved. With the design of a loosely packed QD layer resulting in the direct contact of poly[N,N′-bis(4-butylphenyl)-N,N′-bis(phenyl)benzidine] (poly-TPD) and 2,2′,2″-(1,3,5-benzinetriyl)-tris(1-phenyl-1-H-benzimidazole) (TPBi) in the device, a ternary complementary white QD-LED consisting of blue component (poly-TPD), green component (QDs), and red component (exciplex formed at the interface between poly-TPD and TPBi) has been demonstrated. The resulting white QD-LED shows an excellent color rendering index of 95.